Cardiac vagal tone, a non‐invasive measure of parasympathetic tone, is a clinically relevant tool in Type 1 diabetes mellitus. Issue 10 (17th August 2017) - Brock, C.; Jessen, N.; Brock, B.; Jakobsen, P. E.; Hansen, T. K.; Rantanen, J. M.; Riahi, S.; Dimitrova, Y. K.; Dons‐Jensen, A.; Aziz, Q.; Drewes, A. M.; Farmer, A. D.
Abstract: Aims: To compare a novel index of parasympathetic tone, cardiac vagal tone, with established autonomic variables and to test the hypotheses that (1) cardiac vagal tone would be associated with established time and frequency domain measures of heart rate and (2) cardiac vagal tone would be lower in people with Type 1 diabetes than in a matched healthy cohort and lower still in people with established neuropathy. Methods: Cardiac vagal tone is a validated cardiometrically derived index of parasympathetic tone. It is measured using a standard three‐lead electrocardiogram which connects, via Bluetooth, to a smartphone application. A 5‐min resting recording of cardiac vagal tone was undertaken and observational comparisons were made between 42 people with Type 1 diabetes and peripheral neuropathy and 23 without peripheral neuropathy and 65 healthy people. In those with neuropathy, 24‐h heart rate variability values were compared with cardiac vagal tone. Correlations between cardiac vagal tone and clinical variables were also made. Results: C ardiac vagal tone was lower in people with established neuropathy and Type 1 diabetes in comparison with healthy participants [median (interquartile range) linear vagal scale 3.4 (1.6–5.5 vs 7.0 (5.5–9.6); P  <   0.0001]. Cardiac vagal tone was positively associated with time ( r  =   0.8, P  <   0.0001) and frequency domain markers of heart rate variability ( r  =   0.75, P  <   0.0001), representing established measures of parasympathetic function. Cardiac vagal tone was negatively associated with age ( r =–0.32, P  =   0.003), disease duration ( r =–0.43, P  <   0.0001) and cardiovascular risk score ( r =–0.32, P  =   0.006). Conclusions: Cardiac vagal tone represents a convenient, clinically relevant method of assessing parasympathetic nervous system tone, potentially facilitating the earlier identification of people with Type 1 diabetes who should undergo formal autonomic function testing. What's new?: Cardiac autonomic neuropathy (CAN) is common and related to morbidity and mortality. In people with diabetes, CAN reduces quality of life and increases mortality. The clinical manifestations of CAN are pleomorphic and are under‐recognized and thus under‐diagnosed, arguably because of a lack of availability/access to objective testing. We present a novel, near‐patient, easily interpretable technique that is closely correlated with traditional techniques and has clinical salience.